1993
DOI: 10.1302/0301-620x.75b1.8421009
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding nerve damage during elbow arthroscopy

Abstract: To define the anatomical relationships of the nerves to the common arthroscopy portals at the elbow an arthroscope was introduced into 20 cadaver elbows and the positions of the nerves were then determined by dissection. In all cases the posterior interosseous nerve lay close to the radiohumeral joint and to the anterolateral portal. Pronation of the forearm displaced the nerve away from the arthroscope. The median nerve passed consistently within 14 mm of the arthroscope when it was introduced through the ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
67
0
6

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(77 citation statements)
references
References 3 publications
4
67
0
6
Order By: Relevance
“…The mean distance between the radial nerve and the anterolateral portal was measured as 9.1 mm at 90°of flexion and 4.7 mm during extension. On the other hand, Marshall et al 11 reported that pronation of the forearm resulted in an increase in the distance of the radial nerve from the portal route.…”
Section: Discussionmentioning
confidence: 99%
“…The mean distance between the radial nerve and the anterolateral portal was measured as 9.1 mm at 90°of flexion and 4.7 mm during extension. On the other hand, Marshall et al 11 reported that pronation of the forearm resulted in an increase in the distance of the radial nerve from the portal route.…”
Section: Discussionmentioning
confidence: 99%
“…Arthroscopic release is challenging because the neurovascular structures are close to the portals and the restricted working space afforded to the congruity of the joint and noncompliant capsule. 6,17,19,27 Early reports of arthroscopic elbow capsule release documented nerve injuries, but the safety profile has improved safety over time. (7 ) in the open group.…”
Section: Discussionmentioning
confidence: 99%
“…The mean distance of the DALP to the radial nerve has been reported from 4.0 to 7.2 mm. [7][8][9][10]12 The posterior antebrachial cutaneous nerve is approximately 7.6 to 12.6 mm away. 8,10 To avoid this risk of injury, many surgeons advocate moving this portal more proximal.…”
mentioning
confidence: 99%
“…Given its transtendinous location, it is relatively safe from surrounding neurovascular structures. 7,8,10 Posterolateral Portal. The posterolateral portal is located along the lateral border of the triceps tendon approximately 1 cm anterior to the midpoint of a line connecting the olecranon and the LE.…”
mentioning
confidence: 99%